Screening Adherence for Depression Post Stroke: Evaluation of Outpatients, a London Experience (SAD PEOPLE). Issue 1 (2nd January 2019) - MacKenzie, Heather M; Rice, Danielle; Teasell, Robert; Macaluso, Steven
ABSTRACT: Background : Post stroke depression (PSD) is common, and the transition home following discharge may be especially challenging for stroke survivors. Objectives : This study aimed to determine how well specific Canadian Best Practice Recommendations for PSD screening were adopted within a stroke rehabilitation outpatient clinic before and after the utilization of a standardized clinical form. Methods : Practices were evaluated through retrospective chart review before and after the implementation of the standardized form which cued physicians to administer the Patient Health Questionnaire 9 (PHQ-9) at the first outpatient visit. Participants included those aged ≥18 years with a primary diagnosis of stroke. Results : One hundred thirty-five subjects' charts were reviewed. Form implementation was associated with increased rates of PSD screening (93.8% versus 0%) and charting regarding mood (55.4% versus 15.7%). Conclusion : This study highlights the frequency of depressive symptoms in an outpatient cohort and demonstrates how screening rates can be improved by using a standardized form. Routine PHQ-9 completion at the first outpatient visit was associated with more physician–patient discussion and documentation regarding mood.